Effects of fluoride on in vitro hydroxyapatite demineralisation analysed by 19F MAS-NMR - Ferizoli, Bajram; Cresswell-Boyes, Alexander J.; Anderson, Paul; Lynch, Richard J. M.; Hill, Robert G. (Frontiers in Dental Medicine, 2023)
Introduction Fluoride plays a major role in inhibiting enamel dissolution and promoting fluorapatite formation. Porous hydroxyapatite (HAP) discs can be used as an enamel analogue in artificial demineralisation/remineralisation studies. Method The aim of the study was to monitor the fluoride-mineral phases formed on HAP surfaces as a function of fluoride concentration ([F−]) under demineralising conditions, using 19F magic angle spinning nuclear magnetic resonance (MAS-NMR) spectroscopy, and compare the results with a previous study using an enamel substrate. Porous HAP blocks were immersed in demineralisation solutions (0.1 M acetic acid, pH 4.0) with increasing [F−] (0–1450 ppm). Results At below 50 ppm [F−], 19F MAS-NMR showed fluoride-substituted apatite formation; above 50 ppm [F−], calcium fluoride (CaF2) was formed in increasing proportions. These results mirrored those of previous similar studies with an enamel substrate. Further increases in fluoride caused no further measurable reduction in demineralisation but increased the proportion of CaF2 formed. The total calcium concentration [Ca] and total phosphorus [P] concentrations in the solution were measured by inductively coupled plasma atomic emission spectroscopy. At high fluoride concentrations, the solution total [P] increased, and the molar Ca:P ratios decreased to values consistent with the formation of CaF2. However, Ca:P ratios found at low [F−] were higher than those in the previous enamel study and consistent with the formation of a partially fluoridated apatite. Conclusions Under demineralising conditions, CaF2 formed on HAP at an [F−] of 50 ppm and above, whereas fluoridated apatite formed at an [F−] below 50 ppm. The results were consistent with those obtained when an enamel substrate was used.